Cruisers' satisfaction with shore experience: An empirical study on a China-Japan itinerary. (1st November 2019) - Sun, Xiaodong; Xu, Meihua; Lau, Yui-yip; Gauri, Dinesh K.
Abstract: The cruise industry has become one of the most rapidly developing segments of the entire tourism market. Although, globally, the cruising sector is comprised of predominately North American and European companies, the Asia Pacific region's cruise industry has reported exciting growth rates in recent years. Especially in an emerging cruise market, it is critical to continuously attract potential cruisers by improving service quality and tourist satisfaction. The purpose of this article is to evaluate cruiser satisfaction with shore excursions or activities through an empirical study on a China-Japan itinerary starting from Shanghai Wusongkou International Cruise Port in China. First, we identify a satisfaction index system based on a broad literature review. Based on data collected from a questionnaire distributed to cruisers embarking from Shanghai, we use a multiple criteria decision-making method to evaluate and identify the gaps between the cruisers' average satisfaction and the aspired level of satisfaction with various criteria for a high-quality shore experience are identified. Finally, we propose some managerial implications for ports of call working to improve the quality of their shore excursions and activities. The results derived from the current study could significantly contribute to cruise itinerary planning. Highlights: This article offers a case study on the China-Japan cruise itinerary starting from Shanghai, the largest cruise port in China. An index system is established for evaluating Chinese cruisers' satisfaction with shore experience. The gaps between the cruisers' average satisfaction and the aspired level of satisfaction with various criteria for a high-quality shore experience are identified. Improving the quality of shore excursions and activities to enhance cruise liners competitive advantages are provided..